Viability of Split Thickness Autogenous Skin Transplantation in Canine Distal Limb Reconstruction – An Experimental Evaluation - M. S. Ijaz, A. K. Mahmood, N. Ahmad1, M. A. Khan, and U. Farooq (Pakistan Veterinary Journal, 2012)
Distal limb reconstruction is complicated by the paucity of local tissues and the frequent association of orthopedic injury with cutaneous loss. Though, second-intention healing or skin stretching techniques are used for wounds involving less than a 30% circumference of the limb, however, skin grafts are recommended for reconstruction of larger superficial wounds. The present study was designed to clinically evaluate the viability of split thickness autogenous skin transplantation (STAST) in dogs. Standardized surgical defects of variable size i.e. 3×3, 4×4 and 5×5 sq cm were made on the left middle radial area (forearm) of 15 mongrel dogs assigned to Group A, B and C, respectively having 5 dogs each. Split thickness autogenous skin grafts were harvested from mid thorax and placed in these defects through several simple interrupted sutures. Results indicated a success rate of 80% with no clinical difference in the survival rate of three different sizes of grafts used. Hence, STAST can successfully be used for canine distal limb reconstruction.